Species of Sulfur in Sour Gas Reservoir: Insights from In Situ Raman Spectroscopy of S–H2S–CH4–H2O System and Its Subsystems from 20 to 250°C. (23rd March 2021) - Yu, Yifan; Hu, Wenxuan; Chou, I-Ming; Jiang, Lei; Wan, Ye; Li, Yiqun; Xin, Yang; Wang, Xiaolin
Abstract : Thermochemical sulfate reduction (TSR) is the most important mechanism for the generation of high-concentration H2 S in gas reservoirs. Sulfur speciation in sour gas is one of the key factors controlling the rate and extent of TSR in gas reservoirs. However, experimental studies on S species in sour gas are limited due to the toxicity and corrosion of S and H2 S. Fused silica capillary capsules (FSCCs) are inert to S and H2 S and, therefore, were employed in this study as microreactors containing the S–H2 S–CH4 –H2 O system and its subsystems, representing the composition of sour gas. The in situ Raman spectra of each system were collected continuously during the process of heating from 20°C to 250°C. The results showed the following: (1) a Raman peak at 2500 cm −1 was detected in the liquid S phase of the S–H2 S–CH4 –H2 O system at 120–250°C, which was attributed to H2 Sn . A Raman band at 533 cm −1 was detected in the aqueous phase of the S–H2 S–H2 O–CH4 system at 250°C and was assigned to S3 −, suggesting that S3 − and H2 Sn are important S species in sour gas reservoirs at elevated temperatures. (2) The Raman peak at 2500 cm −1 disappeared at 20°C, indicating that H2 Sn decomposes into S and H2 S. During gas extraction, the decomposition of H2 Sn will cause S deposition in pipelines. (3) In addition to S3 −, H2 Sn could be the intermediate valence S species involved in the TSR reaction.